EQUILIBRIUM THEORY APPROACH TO COMPLETING BANKRUPTCY: BALANCING THE RIGHTS OF CREDITORS AND DEBTORS IN THE ERA OF THE DIGITAL ECONOMY - Indah Maulani; Karisma Cakraningrat; Devi Yuandhita Prameswari (Fakultas Hukum Universitas Jenderal Soedirman, 2025)
In bankruptcy cases, creditors’ claims to a debtor’s assets are frequently underrated especially when those assets are technology‑based or intellectual property. Because existing valuation systems lag behind digital realities, case resolutions often tilt unfairly between creditor and debtor interests.The purpose of the research is to explore a legal approach through equilibrium theory to analyze the settlement of bankruptcy cases between creditors and debtors, as well as to evaluate whether bankruptcy regulations in Indonesia are adequate in accommodating the development of the digital economy. This research is based on a research method with a normative juridical approach. The results of this study finds that applying equilibrium theory to bankruptcy law balances creditor and debtor interests—accounting for claim priorities, debtor rights, personal assets, and debt restructuring. Indonesia’s bankruptcy framework must now evolve for the digital economy through a more adaptive, transparent, and sustainable legal approach.